PENGARUH EXCHANGE RATE, MULTINATIONALITY, DAN LEVERAGE TERHADAP TRANSFER PRICING - Divinia Mayzura; Prima Apriwenni (Jurnal Akuntansi, 2023)
Transfer pricing can be refered as a company step to determine the transfer price of a transaction by company. There are two forms of transactions in transfer pricing, inter-company and intra-company. The transaction itself can be done in one country, or multiple countries. Based on the purposive sampling method, the samples obtained were 11 companies during 3 years of observation bring the result of 33 observation data. Observation data collected from Manufacture company audited report and registered in Indonesia Stock Exchange. The analysis technique used multiple linear regression with pooling data, classic assumption test, F test, t test, and R2 test. The result from this research showed that the exchange rate variable has no influence to company decision for practicing transfer pricing. The variable multinationality has a negative influence on the company decision to transfer pricing. Thus, the leverage variable has positive influence toward the company decision to practice transfer pricing.